Hypoaldosteronism syndrome in children and adolescents - V. V. Smirnov; A. E. Saparova (Лечащий Врач)
The review article describes the current data on the etiology, pathogenesis, clinical features, genetic diagnosis, and treatment tactics for hypoaldosteronism in children and adolescents. Phenotypic signs typical for this syndrome are described.